Scaling up high‐impact interventions: How is it done?. (23rd June 2015) - Smith, Jeffrey Michael; de Graft‐Johnson, Joseph; Zyaee, Pashtoon; Ricca, Jim; Fullerton, Judith
Abstract: Building upon the World Health Organization's ExpandNet framework, 12 key principles of scale‐up have emerged from the implementation of maternal and newborn health interventions. These principles are illustrated by three case studies of scale up of high‐impact interventions: the Helping Babies Breathe initiative; pre‐service midwifery education in Afghanistan; and advanced distribution of misoprostol for self‐administration at home births to prevent postpartum hemorrhage. Program planners who seek to scale a maternal and/or newborn health intervention must ensure that: the necessary evidence and mechanisms for local ownership for the intervention are well‐established; the intervention is as simple and cost‐effective as possible; and the implementers and beneficiaries of the intervention are working in tandem to build institutional capacity at all levels and in consideration of all perspectives.